Preparation method and application of a steel slag stabilizing agent material

CN122916480APending Publication Date: 2026-10-16SHENYANG JIANZHU UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611168287.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]针对以上现有技术的不足,本发明提供了一种钢渣稳安剂材料及其制备方法,以解决现有技术中钢渣体积膨胀抑制方法存在的处理周期长、资源占用大、抑制效果有限及长期稳定性差的问题

Benefits of technology

[0023] 1. This invention combines organic chelating agents with inorganic stabilizing components through the bridging effect of coupling agents, thereby constructing a stable organic-inorganic coupling chelating system. This system not only leverages the efficient complexing ability of chelating agents for free calcium ions, but also utilizes the hydration reaction of inorganic powders to generate a dense coating layer, achieving a synergistic stabilizing effect of chemical passivation and physical sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916480A_ABST
    Figure CN122916480A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a steel slag stabilizing agent material, and belongs to the technical field of steel slag aggregate treatment. The steel slag stabilizing agent material is composed of a precursor organic chelation component (A material) and a later-stage composite stabilizing component (B material). According to mass parts, the raw materials of the A material include 2-5 parts of a silane coupling agent, 3-5 parts of an organic salt chelating agent, 1.35-1.9 parts of acetic acid and 88.1-93.65 parts of water; the raw materials of the B material include 40-70 parts of mineral powder, 15-30 parts of fly ash, 10-20 parts of iron tailing powder, 4-6 parts of an alkali activator and 1-4 parts of a water reducing agent. The precursor organic chelation and the later-stage composite stabilizing technology are combined, the chelation is used to chelate free calcium oxide and free magnesium oxide in the steel slag, calcium ions which are easy to hydrate are formed, and when the composite stabilizing material contacts with the calcium ions, C-S-H and C-A-S-H and other hydration products can be quickly generated, so that the volume expansion of the steel slag aggregate can be quickly, efficiently and stably inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of steel slag aggregate treatment technology, specifically relating to a method for preparing and applying a steel slag stabilizer material. Background Technology

[0002] Steel slag, an industrial solid waste generated during steel smelting, has a huge annual emission volume. Currently, steel slag has been utilized in several fields, with its use as road engineering material and backfill material being one of the effective ways to achieve large-scale utilization, offering good comprehensive benefits. However, steel slag suffers from significant volume expansion during engineering applications. Steel slag contains unstable components such as free calcium oxide (f-CaO) and free magnesium oxide (f-MgO), which undergo hydration reactions upon contact with water to produce calcium hydroxide and magnesium hydroxide, accompanied by significant volume expansion. This leads to cracking and disintegration of the steel slag aggregate, severely affecting its volume stability and long-term durability as an engineering material, becoming a major technical factor limiting the large-scale engineering application of steel slag.

[0003] Currently, the common method for addressing the volume expansion problem of steel slag is natural aging, which involves leaving steel slag in the open for 2-3 years to allow the free calcium oxide and free magnesium oxide to fully decompose in the natural environment before reuse. While this method is simple to operate, the aging period is long, it occupies a large amount of land resources, significantly increasing the economic costs of storage and management. Furthermore, the dust and alkaline leachate generated during long-term open-air storage of steel slag pose a significant pollution risk to the surrounding environment.

[0004] To address the aforementioned issues, existing technologies have included research on using mineral admixtures to suppress the volume expansion of steel slag. By incorporating active mineral materials such as fly ash and slag powder into steel slag, the pozzolanic reaction consumes some free calcium oxide, which can reduce the expansion rate to some extent. However, this method has a slow reaction rate, making it difficult to effectively eliminate the instability of steel slag in a short time, resulting in limited suppression. In addition, some studies have used organic materials such as silicone resins to seal the pores on the surface of steel slag through spraying or hydrophobic treatment, reducing the contact between moisture and unstable components inside the steel slag, thereby suppressing its volume expansion. While these methods can achieve good suppression effects, silicone resins suffer from drawbacks in practical use, including long-term aging and failure, uneven spray distribution, easy adhesion between steel slag particles, and high material costs, which restrict their large-scale application in engineering projects.

[0005] Therefore, developing a treatment method that can efficiently, economically, and stably suppress the volume expansion of steel slag in the long term, and enabling the large-scale application of steel slag in practical engineering, is of great significance for realizing the recycling of steel slag waste and promoting the sustainable development of the steel industry. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this invention provides a steel slag stabilizer material and its preparation method, thereby solving the problems of long processing cycles, high resource consumption, limited inhibition effects, and poor long-term stability in existing methods for inhibiting steel slag volume expansion. Specifically, this is achieved through the following techniques.

[0007] This invention provides a steel slag stabilizer material, which is composed of a precursor organic chelating component (A component) and a subsequent composite stabilizer component (B component). By mass, the precursor organic chelating component (A component) includes 2-5 parts of silane coupling agent, 3-5 parts of organic salt chelating agent, 1.35-1.9 parts of acetic acid, and 88.1-93.65 parts of water; the subsequent composite stabilizer component (B component) includes 40-70 parts of mineral powder, 15-30 parts of fly ash, 10-20 parts of iron tailings powder, 4-6 parts of alkali activator, and 1-4 parts of water-reducing agent.

[0008] Further, by mass, the precursor organic chelating component (material A) raw materials include 5 parts of silane coupling agent, 5 parts of organic salt chelating agent, 1.8 parts of acetic acid, and 88.2 parts of water; the subsequent composite stabilizing component raw materials include 65 parts of mineral powder, 18 parts of fly ash, 12 parts of iron tailings powder, 4 parts of alkali activator, and 1 part of water reducing agent.

[0009] Furthermore, in the precursor organic chelating component (material A) raw material, the silane coupling agent is selected from one or more of aminopropyltriethoxysilane, vinyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and vinylsilane; the organic salt chelating agent is selected from one or more of disodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, and sodium gluconate.

[0010] Furthermore, in the raw materials of the later-stage composite stabilizing component (B material), the ore powder is selected from one or two of S95 grade and S105 grade blast furnace slag powder; the fly ash is selected from one or two of Grade I and Grade II fly ash; the alkali activator is selected from one or more of sodium metasilicate, sodium carbonate, sodium hydroxide and calcium hydroxide; and the water-reducing agent is a naphthalene-based water-reducing agent.

[0011] This invention employs a synergistic mechanism of pre-treatment organic chelation and post-treatment composite stabilization to treat steel slag aggregate. In the pre-treatment stage involving the addition of component A, the weakly acidic environment provided by the acetic acid aqueous solution induces the dissolution of calcium and magnesium ions from free calcium oxide (f-CaO) and free magnesium oxide (f-MgO) on the steel slag surface. The organic salt chelating agent then coordinates and chelates with these ions, transforming them into stable active complexes and eliminating the potential expansion of free oxides. Simultaneously, the silane coupling agent, after hydrolysis, condenses with hydroxyl groups (-OH) on the steel slag surface to form strong chemical bonds, introducing organic functional groups into the aggregate surface. This improves the wettability and reactivity of the steel slag surface and, through the bridging effect of the coupling agent, forms a chemical bond between the inorganic steel slag surface and the subsequent organic / inorganic composite cementitious system, effectively enhancing the interfacial bonding between component B and the steel slag aggregate.

[0012] After the addition of component B, the active silica (SiO2) and alumina (Al2O3) in the mineral powder and fly ash undergo a hydration reaction under the alkaline activation of sodium metasilicate, aided by moisture on the aggregate surface and in the environment. This hydration combines with calcium and magnesium ions released from the active calcium and magnesium ion complexes already formed in component A, generating CSH and CASH gels in situ. This tightly binds the steel slag particles and forms a dense coating layer on the outer layer of the aggregate, filling surface pores and microcracks while physically sealing residual free oxides. The iron tailings powder fills the pores, optimizing the gradation, while the naphthalene-based water-reducing agent disperses the cementitious particles, ensuring a uniform distribution of hydration products.

[0013] Thus, the chemical chelation of material A, combined with the physical encapsulation and chemical bonding of material B, creates a stable structure on the surface of the steel slag aggregate from the inside out, effectively suppressing the volume expansion of the steel slag aggregate and solving the volume stability problem in its engineering applications such as road base courses and mine backfilling.

[0014] Furthermore, the preparation method of the steel slag stabilizer material includes the following steps:

[0015] The acetic acid aqueous solution is mixed with the silane coupling agent and stirred until homogeneous. Then, an organic salt chelating agent is added and the mixture is stirred until homogeneous again to obtain the precursor organic chelating component (material A).

[0016] The mineral powder, fly ash and iron tailings powder are mixed evenly, and the alkali activator and water-reducing agent are added and mixed evenly to obtain the later composite stabilizing component (B material).

[0017] Furthermore, the mixing time for adding the organic salt chelating agent is 20-30 minutes; the mixing time for adding the alkali activator and water-reducing agent is 15-30 minutes. Controlling the mixing time for 20-30 minutes after adding the organic salt chelating agent to material A ensures that after thorough mixing, some of the coupling agent combines with the chelating agent to form a cross-linked complex, while also allowing a certain amount of the coupling agent to chemically react with the steel slag and material B respectively, thus acting as a bridge. Controlling the mixing time for 15-30 minutes after adding the auxiliary alkali activator and water-reducing agent to material B ensures that the auxiliary materials are fully and uniformly dispersed in the large amount of main powder, avoiding localized anhydrous activation effects caused by uneven dispersion.

[0018] A second aspect of the present invention provides the application of the above-mentioned steel slag stabilizer material in steel slag aggregates.

[0019] Furthermore, the treatment method of the steel slag stabilizer material is as follows: after spraying the precursor organic chelating component onto the surface of the steel slag aggregate, it is naturally air-dried for 30 min to 90 min; then, the composite stabilizer component is mixed with water and coated onto the surface of the steel slag aggregate, and cured under natural conditions for 72 h to 120 h.

[0020] Furthermore, based on the mass of the steel slag aggregate, the amount of the precursor organic chelating component is 3% to 6%, and the amount of the composite stabilizing component is 10% to 30%.

[0021] Furthermore, based on the mass of the composite stabilizing component, the amount of water added is 0.32%~0.38%.

[0022] Compared with the prior art, the advantages of the present invention are:

[0023] 1. This invention combines organic chelating agents with inorganic stabilizing components through the bridging effect of coupling agents, thereby constructing a stable organic-inorganic coupling chelating system. This system not only leverages the efficient complexing ability of chelating agents for free calcium ions, but also utilizes the hydration reaction of inorganic powders to generate a dense coating layer, achieving a synergistic stabilizing effect of chemical passivation and physical sealing.

[0024] 2. This invention converts the free calcium oxide on the surface of steel slag into a stable complex through a pre-chelation treatment, eliminating the chemical cause of volume expansion from the source; at the same time, the subsequent composite stabilizing component forms a dense coating layer on the surface of the aggregate, reducing the contact rate between the remaining free calcium and moisture, and further inhibiting the occurrence of volume expansion of steel slag.

[0025] 3. The stabilizer and treatment method provided by this invention endow the steel slag aggregate with hydrophobic properties and strengthen the aggregate interface structure. The volume stability of the treated steel slag aggregate is significantly improved, which can meet the requirements of road base courses, mine pit backfilling and other projects for aggregate durability and road performance, and realize the resource utilization of steel slag. Attached Figure Description

[0026] Figure 1 This is a comparison chart of the expansion rates of steel slag aggregates from Example 1 and Comparative Example 1 after stabilization treatment. Detailed Implementation

[0027] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] The present invention provides a method for preparing a steel slag stabilizer material, comprising the following steps:

[0029] S1. Prepare an aqueous solution of acetic acid. Slowly inject the silane coupling agent into the acetic acid solution and stir until the solution is clear and transparent. Then inject the organic chelating agent and continue stirring and mixing until the solution is uniform to obtain the precursor organic chelating component (material A).

[0030] S2. Mix the mineral powder and fly ash until the color is uniform, add iron tailings powder and continue mixing until the color is uniform, add alkali activator and water reducing agent, and continue mixing until uniform to obtain the later composite stable component (B material).

[0031] In some embodiments, by weight, the amount of raw material A can be 2-5 parts of silane coupling agent, 3-5 parts of organic salt chelating agent, 1.35-1.9 parts of acetic acid, and 88.1-93.65 parts of water; the amount of raw material B can be 40-70 parts of mineral powder, 15-30 parts of fly ash, 10-20 parts of iron tailings powder, 4-6 parts of alkali activator, and 1-4 parts of water-reducing agent.

[0032] In some embodiments, the silane coupling agent in the raw materials of material A may be selected from one or more of aminopropyltriethoxysilane, vinyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and vinylsilane; the organic salt chelating agent may be selected from one or more of disodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, and sodium gluconate.

[0033] In some embodiments, the raw materials of material B may include mineral powder selected from one or two of S95 grade and S105 grade blast furnace slag powder; fly ash selected from one or two of grade I and grade II fly ash; alkali activator selected from one or more of sodium metasilicate, sodium carbonate, sodium hydroxide, and calcium hydroxide; and water-reducing agent selected from naphthalene-based water-reducing agent.

[0034] In some embodiments, the mixing and stirring time after injecting the organic chelating agent in step S1 can be 20 min to 30 min, and the mixing and stirring time after adding the alkali activator and water-reducing agent in step S2 can be 15 min to 30 min.

[0035] Example 1

[0036] This embodiment provides a method for preparing a steel slag stabilizer material, including the following steps:

[0037] S1. Add 1.8g of acetic acid to 98.2g of deionized water and stir at 300rpm for 30s to obtain an acetic acid aqueous solution with a concentration of 1.8%. Take 93g of the above acetic acid aqueous solution into a 500mL beaker, place the beaker on a magnetic stirrer, set the speed to 1200rpm and stir slowly. Slowly add 3g of vinyltrimethoxysilane and stir for 5min until the solution is clear and transparent. Then add 4g of disodium ethylenediaminetetraacetate and continue stirring for 25min until the solution is uniformly mixed, thus obtaining the precursor organic chelate component (material A).

[0038] S2. Take 55g of S95 grade slag powder and 22g of grade II fly ash and place them in a dry powder mixer and stir for 5 minutes; add 15g of ultrafine iron tailings powder and continue stirring for 5 minutes until the color becomes uniform; finally, add 6g of anhydrous sodium metasilicate and 2g of naphthalene-based high-efficiency water-reducing agent and continue mixing for 20 minutes to obtain the later-stage composite stable component (material B).

[0039] Example 2

[0040] This embodiment provides a method for preparing a steel slag stabilizer material, including the following steps:

[0041] S1. Add 2g of acetic acid to 98g of deionized water and stir at 300rpm for 30s to obtain a 2% acetic acid aqueous solution. Take 90g of the above acetic acid aqueous solution into a 500mL beaker, place the beaker on a magnetic stirrer, set the speed to 1500rpm and stir slowly, add 5g of vinylsilane, stir for 5min until the solution is clear and transparent; then add 5g of dipotassium ethylenediaminetetraacetate and continue stirring for 30min until the solution is uniformly mixed, thus obtaining the precursor organic chelate component (material A).

[0042] S2. Take 65g of S105 grade slag powder and 18g of grade I fly ash and place them in a dry powder mixer and stir for 5 minutes; add 12g of ultrafine iron tailings powder and continue stirring for 5 minutes until the color becomes uniform; finally, add 4g of anhydrous sodium metasilicate and 1g of naphthalene-based high-efficiency water-reducing agent and continue mixing for 25 minutes to obtain the later-stage composite stable component (material B).

[0043] Comparative Example 1

[0044] This embodiment provides a method for preparing a steel slag stabilizer material, which is basically the same as that in Example 1, except that:

[0045] In step S1, disodium ethylenediaminetetraacetate (an organic chelating agent) is not added.

[0046] Comparative Example 2

[0047] This embodiment provides a method for preparing a steel slag stabilizer material, which is basically the same as that in Example 1, except that:

[0048] In step S1, vinyltrimethoxysilane (silane coupling agent) is not added.

[0049] Comparative Example 3

[0050] This embodiment provides a method for preparing a steel slag stabilizer material, which is basically the same as that in Example 1, except that:

[0051] In step S2, sodium metasilicate (alkali activator) and naphthalene-based water-reducing agent (water-reducing agent) are not added.

[0052] Application example: Stabilization and safety treatment experiment of steel slag aggregate

[0053] The steel slag stabilizer materials prepared in Examples 1-2 and Comparative Examples 1-3 were used for the stabilization treatment of steel slag aggregates, and the steps are as follows:

[0054] 30g of material A prepared in Example 1 was evenly sprayed onto the surface of 1000g of steel slag aggregate using an atomized spraying method, i.e., the spraying amount was 3% of the mass of the steel slag aggregate, and then allowed to air dry for 30 minutes. Next, 100g of material B was mixed with 32g of water to form a slurry, which was then evenly coated onto the surface of the steel slag aggregate treated with material A, i.e., the amount of material B was 10% of the mass of the steel slag aggregate. After thorough mixing, the mixture was cured under natural conditions for 72 hours, thus completing the stabilization treatment. The steel slag aggregates treated with the above stabilization treatment are designated as Steel Slag Aggregate 1.

[0055] 40g of material A prepared in Example 2 was evenly sprayed onto the surface of 1000g of steel slag aggregate using an atomized spraying method, i.e., the spraying amount was 4% of the mass of the steel slag aggregate, and then naturally air-dried for 40 minutes. Next, 300g of material B was mixed with 114g of water to form a slurry, which was then evenly coated onto the surface of the steel slag aggregate treated with material A, i.e., the amount of material B was 30% of the mass of the steel slag aggregate. After thorough mixing, it was cured under natural conditions for 72 hours, thus completing the stabilization treatment. The steel slag aggregates that underwent the stabilization treatment are referred to as Steel Slag Aggregate 2.

[0056] 30g of material A prepared in Comparative Examples 1-3 was uniformly sprayed onto the surface of 1000g of steel slag aggregate using a misting spraying method, i.e., the spraying amount was 3% of the mass of the steel slag aggregate, and then allowed to air dry for 30 minutes. Then, 100g of material B was mixed with 32g of water to form a slurry, which was then uniformly coated onto the surface of the steel slag aggregate treated with material A, i.e., the amount of material B was 10% of the mass of the steel slag aggregate. After thorough mixing, the mixture was cured under natural conditions for 72 hours, thus completing the stabilization treatment. The steel slag aggregates after the above stabilization treatment were designated as steel slag aggregates 3-5.

[0057] 30g of material A prepared in step S1 of Example 1 was evenly sprayed onto the surface of 1000g of steel slag aggregate using an atomized spraying method, i.e., the spraying amount was 3% of the mass of the steel slag aggregate. The aggregate was cured under natural conditions for 72 hours to complete the stabilization treatment. The steel slag aggregates after the stabilization treatment are referred to as steel slag aggregate 6.

[0058] 100g of material B prepared in step S2 of Example 1 was mixed with 32g of water to form a slurry, which was then evenly coated onto the surface of 1000g of steel slag aggregate. The amount of material B used was 10% of the mass of the steel slag aggregate. The mixture was cured under natural conditions for 72 hours to complete the stabilization treatment. The steel slag aggregates that underwent the stabilization treatment are designated as steel slag aggregate 7.

[0059] The autoclaving expansion rate, immersion expansion rate, and volume expansion rate compared with untreated steel slag aggregates 1 to 7 were tested respectively, and the results are shown in Table 1.

[0060] Table 1. Results of autoclaving expansion rate and immersion expansion rate of steel slag aggregates 1-7

[0061] Steel slag aggregate 1 0.08 0.12 Steel slag aggregate 2 0.06 0.09 Steel slag aggregate 3 0.19 0.25 Steel slag aggregate 4 0.21 0.28 Steel slag aggregate 5 0.17 0.22 Steel slag aggregate 6 0.32 0.38 Steel slag aggregate 7 0.24 0.31

[0062] (Note: The autoclaving expansion rate is determined according to GB / T 20491 "Steel slag powder for use in cement and concrete", with a technical requirement of ≤0.5%; the immersion expansion rate is determined according to GB / T 25824 "Determination of immersion expansion rate of steel slag aggregate", with a technical requirement of ≤2.0%.)

[0063] A comparison of the expansion rates of steel slag aggregates 1 and 3 after treatment with the steel slag stabilizer material prepared in Example 1 and Comparative Example 1. Figure 1 As shown.

[0064] As shown in Table 1, the autoclaving expansion rates of steel slag aggregate 1 and steel slag aggregate 2 were 0.08% and 0.06%, respectively, and the water immersion expansion rates were 0.12% and 0.09%, respectively. Their stability and safety effects were significantly better than those of the comparative proportions and the single-component control group.

[0065] From Table 1 and Figure 1 It can be seen that the autoclaving expansion rate and water immersion expansion rate of steel slag aggregate 3 (without organic chelating agent) increased to 0.19% and 0.25%, respectively. The autoclaving expansion rate and water immersion expansion rate of steel slag aggregate 3 were 3 times and 2.6 times that of steel slag aggregate 1, respectively. This indicates that when organic salt chelating agent is lacking, free calcium ions cannot be effectively complexed and transformed, and the expansion inhibition effect is significantly reduced.

[0066] The autoclaving expansion rate and immersion expansion rate of steel slag aggregate 4 (without silane coupling agent) increased to 0.21% and 0.28% respectively, indicating that without silane coupling agent, the organic chelating component in material A cannot form an effective chemical bridge with the inorganic material B. The construction of the organic-inorganic coupling chelate system is incomplete, and the stability effect decreases most significantly.

[0067] The autoclaving expansion rate and immersion expansion rate of steel slag aggregate 5 (without alkali activator and water-reducing agent) were 0.17% and 0.22%, respectively, which were significantly higher than those of Example 1. This indicates that without the alkaline activation of sodium metasilicate and the dispersing effect of naphthalene-based water-reducing agent, the hydration reaction of material B was insufficient and the density of the coating layer decreased, resulting in a decrease in the stability effect.

[0068] The autoclaving expansion rate and immersion expansion rate of steel slag aggregate 6 (A material only) were as high as 0.32% and 0.38% respectively, which were the highest among all samples. This indicates that the surface chelation treatment of A material alone cannot form a sufficient physical coating layer to block the contact between water and free calcium oxide in steel slag. The secondary coating of B material is necessary to achieve effective improvement in volume stability.

[0069] The autoclaving expansion rate and immersion expansion rate of steel slag aggregate 7 (B material only) were as high as 0.24% and 0.31% respectively. This indicates that although B material can form a certain physical encapsulation effect without the A material pre-chelation treatment, it cannot eliminate the expansion risk of free oxides and the stabilization effect is limited.

[0070] In summary, this invention achieves a dual stabilizing effect of chemical chelation and physical cementation on steel slag aggregates through the synergistic cooperation of the precursor organic chelating component and the subsequent composite stabilizing component. Moreover, each functional component is indispensable, and omitting any treatment step will lead to a significant deterioration in the stabilizing effect of steel slag aggregates.

[0071] The above detailed embodiments describe the implementation of the present invention; however, the present invention is not limited to the specific details described in the above embodiments. Within the scope of the claims and technical concept of the present invention, various simple modifications and changes can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

Claims

1. A steel slag stabilizer material, characterized in that, The steel slag stabilizer material is composed of a precursor organic chelating component and a post-construction composite stabilizer component. By mass, the precursor organic chelating component includes 2-5 parts of silane coupling agent, 3-5 parts of organic salt chelating agent, 1.35-1.9 parts of acetic acid, and 88.1-93.65 parts of water. The post-construction composite stabilizer component includes 40-70 parts of mineral powder, 15-30 parts of fly ash, 10-20 parts of iron tailings powder, 4-6 parts of alkali activator, and 1-4 parts of water-reducing agent.

2. The steel slag stabilizer material according to claim 1, characterized in that, By weight, the precursor organic chelating component raw materials include 5 parts of silane coupling agent, 5 parts of organic salt chelating agent, 1.8 parts of acetic acid, and 88.2 parts of water; the subsequent composite stabilizing component raw materials include 65 parts of mineral powder, 18 parts of fly ash, 12 parts of iron tailings powder, 4 parts of alkali activator, and 1 part of water reducing agent.

3. The steel slag stabilizer material according to claim 1, characterized in that, In the precursor organic chelating component raw material, the silane coupling agent is selected from one or more of aminopropyltriethoxysilane, vinyltrimethoxysilane, glycidoxypropyltrimethoxysilane, and vinylsilane; the organic salt chelating agent is selected from one or more of disodium ethylenediaminetetraacetate, dipotassium ethylenediaminetetraacetate, pentasodium diethylenetriaminepentaacetate, and sodium gluconate.

4. The steel slag stabilizer material according to claim 1, characterized in that, In the raw materials of the later-stage composite stabilizing component, the mineral powder is selected from one or two of S95 grade and S105 grade blast furnace slag powder; the fly ash is selected from one or two of grade I and grade II fly ash; the alkali activator is selected from one or more of sodium metasilicate, sodium carbonate, sodium hydroxide, and calcium hydroxide; and the water-reducing agent is a naphthalene-based water-reducing agent.

5. The method for preparing the steel slag stabilizer material according to any one of claims 1 to 4, characterized in that, Includes the following steps: The acetic acid, water and silane coupling agent are mixed and stirred evenly, and the organic salt chelating agent is added and mixed and stirred evenly to obtain the precursor organic chelating component; The mineral powder, fly ash and iron tailings powder are mixed evenly, and the alkali activator and water-reducing agent are added and mixed evenly to obtain the later-stage composite stabilizing component.

6. The method for preparing the steel slag stabilizer material according to claim 5, characterized in that, The organic salt chelating agent is added and mixed for 20-30 minutes; the alkali activator and water-reducing agent are added and mixed for 15-30 minutes.

7. The application of the steel slag stabilizer material according to any one of claims 1 to 4 in steel slag aggregates.

8. The application of the steel slag stabilizer material according to claim 7 in steel slag aggregate, characterized in that, The treatment method for the steel slag stabilizer material is as follows: the precursor organic chelating component is sprayed onto the surface of the steel slag aggregate and then air-dried for 30 to 90 minutes; then the composite stabilizer component is mixed with water and coated onto the surface of the steel slag aggregate, and cured under natural conditions for 72 to 120 hours.

9. The application of the steel slag stabilizer material according to claim 8 in steel slag aggregate, characterized in that, Based on the mass of the steel slag aggregate, the amount of the precursor organic chelating component is 3% to 6%, and the amount of the composite stabilizing component is 10% to 30%.

10. The application of the steel slag stabilizer material according to claim 8 in steel slag aggregate, characterized in that, Based on the mass of the composite stabilizing component, the amount of water added is 0.32%~0.38%.